2018 IEEE Conference on Decision and Control (CDC) 2018
DOI: 10.1109/cdc.2018.8619725
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Reverse-Waterfilling Characterization of Nonanticipative Rate Distortion Function of Vector-Valued Gauss-Markov Processes with MSE Distortion

Abstract: We analyze the asymptotic nonanticipative rate distortion function (NRDF) of vector-valued Gauss-Markov processes subject to a mean-squared error (MSE) distortion function. We derive a parametric characterization in terms of a reverse-waterfilling algorithm, that requires the solution of a matrix Riccati algebraic equation (RAE). Further, we develop an algorithm reminiscent of the classical reverse-waterfilling algorithm that provides an upper bound to the optimal solution of the reverse-waterfilling optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In this paper, we considered certain classes of time-invariant multidimensional Gauss-Markov process which ensure that all matrices in the optimization problem (11) commute by pairs and thus they are simultaneously diagonalizable. As a result of this feature, we showed that the asymptotic reverse-waterfilling characterization of [1] can be simplified considerably and it is equivalent to a reverse-waterfilling algorithm obtained only by the eigenvalues of the involved matrices. For the latter algorithm, we proposed an iterative approach to compute optimally the optimization problem.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this paper, we considered certain classes of time-invariant multidimensional Gauss-Markov process which ensure that all matrices in the optimization problem (11) commute by pairs and thus they are simultaneously diagonalizable. As a result of this feature, we showed that the asymptotic reverse-waterfilling characterization of [1] can be simplified considerably and it is equivalent to a reverse-waterfilling algorithm obtained only by the eigenvalues of the involved matrices. For the latter algorithm, we proposed an iterative approach to compute optimally the optimization problem.…”
Section: Discussionmentioning
confidence: 90%
“…Overall, the previous experiments show that Algorithm 1 is an elegant and more preferable choice to be implemented in modern delay-constrained and computationally-limited devices like the architectures of networked control systems, compared to SDP or [1,Algorithm 1]. It is very fast and adapts extremely well in high dimensional systems (it is scalable).…”
Section: New Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The most computationally efficient way to compute such problems and, additionally, to gain some insight from the solution is via the well-known reverse-waterfilling algorithm ([ 19 ], Theorem 10.3.3), which is however very hard to construct and compute because one needs to employ and solve complicated KKT conditions [ 37 ]. Such effort was recently made for multivariate Gauss-Markov processes under per instant, averaged total and asymptotically averaged total distortion constraints in [ 24 , 41 ].…”
Section: Lower Boundsmentioning
confidence: 99%
“…
In this paper, we revisit the asymptotic reversewaterfilling characterization of the nonanticipative rate distortion function (NRDF) derived for a time-invariant multidimensional Gauss-Markov processes with mean-squared error (MSE) distortion in [1]. We show that for certain classes of time-invariant multidimensional Gauss-Markov processes, the specific characterization behaves as a reverse-waterfilling algorithm obtained in matrix form ensuring that the numerical approach of [1, Algorithm 1] is optimal.
…”
mentioning
confidence: 99%